(untitled) (Indian Journal of Animal Production and Management, 2024)
At many commercial dairy farms, separation of calves from their mother cows and buffaloes is practiced. This separation has significant negative effects on the immunity, health and growth performance of the calves. To overcome the possible effects of mother-calf contacts on cyclic activity, a socially acceptable and inexpensive tool is biostimulation. Biostimulation is the stimulatory effect of bulls, using chemical, visual, olfactory, tactile, and auditory cues to trigger both, behavioral and endocrine responses in females. This paper discusses the effects of cow-calf contact systems and cow-bull stimulus (biostimulation) on behaviour, performance and welfare of mothers and their calves especially in indigenous breeds of cattle and buffaloes. This literature review concludes that calf-cow contact is very important for both mother and calves especially in native dairy cattle and buffaloes. Free choice colostrum feeding for up to five days to calves and fulltime contact with mother during this period followed by housing of calves in a fenceline contact with mothers for about 4-5 months was found to be an effective strategy to bring out substantial overall improvement in performance, health and welfare of both mothers and their calves. It further shows that the negative consequences on cow-calf contact in terms of delayed onset of ovarian cyclicity can be effectively overcome by keeping a bull in direct or fenceline contact with mother cows and buffaloes after about a month after calving.